2000
DOI: 10.1021/es0000697
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Source-Dependent Bioavailability in Determining the Transfer of Ingested Radionuclides to Ruminant-Derived Food Products

Abstract: The transfer of radioactivity to the milk and meat of farm animals is likely be a major exposure pathway of human populations, following an environmental release of radioactivity. The importance of source-dependent bioavailability in determining absorption from the ruminant gastrointestinal tract of the radiologically significant radionuclides (radiocesium, radiostrontium, radioiodine, and plutonium) is reviewed. The requirements for and suitability of in vitro methods of determining bioavailability for absorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 60 publications
5
50
1
Order By: Relevance
“…Higher DMI's lead to a faster gut passage time [11] prompting the suggestion that absorption of radiocaesium in the gut may be reduced. However, in a previous study we found that the influence of DMI on radiocaesium absorption in sheep was minimal [2] and similar absorption values have been determined for radiocaesium for sheep in a large number of studies and also dairy cattle [12]. An increase in cellular metabolism with increasing food intake has previously been observed, the activity of Na+, K+-ATPase varying with food intake [4]; such an effect could influence the movement of Cs across cell membranes.…”
Section: Protein Turnover Rate and Radiocaesium Transfersupporting
confidence: 69%
“…Higher DMI's lead to a faster gut passage time [11] prompting the suggestion that absorption of radiocaesium in the gut may be reduced. However, in a previous study we found that the influence of DMI on radiocaesium absorption in sheep was minimal [2] and similar absorption values have been determined for radiocaesium for sheep in a large number of studies and also dairy cattle [12]. An increase in cellular metabolism with increasing food intake has previously been observed, the activity of Na+, K+-ATPase varying with food intake [4]; such an effect could influence the movement of Cs across cell membranes.…”
Section: Protein Turnover Rate and Radiocaesium Transfersupporting
confidence: 69%
“…Considerably lower absorption (20e30%) was suggested for reindeer on a lichen diet by Holleman et al (1971), but this is evidently too low to fit the activity concentrations observed in the experiments presented here. Higher factors for true absorption of radiocaesium from forage (mostly within the range 0.6e0.9) have been reported for sheep and cattle (various papers reviewed by Beresford et al, 2000).…”
Section: Discussionmentioning
confidence: 90%
“…The considerably higher activity concentration of refused feed compared to that of offered feed is likely to have been a consequence of the animals selecting against feed with especially high silt contents. The availability of 137 Cs associated with silt from the Ravenglass Estuary for absorption in the ruminant gut has previously been shown to be <10% of that for Cs incorporated into vegetation or ingested as CsCl (see review by Beresford et al, 2000). Apart from Cs there is only limited evidence to suggest that the availability for absorption in the ruminant gut of Am and Pu from saltmarsh vegetation and soil contaminated by marine discharges from the Sellafield reprocessing plant is low compared to 'recommended' values (see Ham et al, 1989;Harrison, 1991;Cooke et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…However, the majority of radiocaesium associated with saltmarsh vegetation is due to adherent silt. The availability for absorption of radiocaesium from silt contaminated by Sellafield marine discharges is <10% (Beresford et al, 2000) compared to that for milk of circa 100% . Milk was, therefore, likely to contribute approximately 75% of the ingested 137 Cs available for absorption by the lambs of the study ewes (at 10 weeks old).…”
Section: Field Milking Studymentioning
confidence: 95%
See 1 more Smart Citation